Polyvinylсhloride‐based anion exchanger for efficient removal of chromium (VI) from aqueous solutions. (1st June 2021) - Bekchanov, Davron; Mukhamediev, Mukhtar; Lieberzeit, Peter; Babojonova, Gulbakhor; Botirov, Sunnat
Abstract: Chemical modification of plasticized polyvinylchloride with polyethylenepolyamine leads to anion exchange resin (PPE‐1). Different characterization techniques, such as XRD, FTIR, and SEM of PPE‐1 anion exchanger revealed weak base amino groups as well as macroporous structure morphology. PPE‐1 turned out effective to remove hexavalent chromium ions from aqueous media. Corresponding adsorption kinetics best fit the pseudo‐second order model that followed a Freundlich isotherm. In the case of hexavalent chromium ions, the maximum adsorption capacity of PPE‐1 was 218.4 mg/g. Thermodynamic data revealed spontaneous endothermic processes and a chemisorption reaction. In addition, results show that the anion exchanger (PPE‐1) has 98% for removing hexavalent chromium ions containing from wastewater.